Targeting the innate repair receptor to treat neuropathy. (July 2016) - Dahan, Albert; Brines, Michael; Niesters, Marieke; Cerami, Anthony; van Velzen, Monique
Abstract : Abstract: The innate repair receptor (IRR) is a heteromer of the erythropoietin receptor and the β-common (CD131) receptor, which simultaneously activates anti-inflammatory and tissue repair pathways. Experimental data suggest that after peripheral nerve injury, the IRR is upregulated in the spinal cord and modulates the neurogenic inflammatory response. The recently introduced selective IRR agonist ARA290 is an 11-amino acid peptide initially tested in animal models of neuropathy. After sciatic nerve injury, ARA290 produced a rapid and long-term relief of mechanical and cold allodynia in normal mice, but not in animals with a β-common receptor knockout phenotype. In humans, ARA290 has been evaluated in patients with small fiber neuropathy associated with sarcoidosis or type 2 diabetes (T2D) mellitus. In patients with sarcoidosis, ARA290 significantly improved neuropathic and autonomic symptoms, as well as quality of life as assessed by the small fiber neuropathy screening list questionnaire. In addition, ARA290 treatment for 28 days initiated a regrowth of small nerve fibers in the cornea, but not in the epidermis. In patients with T2D, the results were similar to those observed in patients with sarcoidosis along with an improved metabolic profile. In both populations, ARA290 lacked significant adverse effects. These experimental and clinical studies show that ARA290 effectively reprograms a proinflammatory, tissue-damaging milieu into one of healing and tissue repair. Further clinical trials with long-term treatment and follow-up are needed to assess the full potential of IRR activation by ARA290 as a disease-modifying therapy in neuropathy of various etiologies.